Incidence of herpes zoster, 1997-2002. - Mullooly, J. P. (Cambridge University Press, 2005)
We estimated age-specific herpes zoster (HZ) incidence rates in the Kaiser Permanente Northwest Health Plan (KPNW) during 1997-2002 and tested for secular trends and differences between residents of two states with different varicella vaccine coverage rates. The cumulative proportions of 2-year-olds vaccinated increased from 35% in 1997 to 85% in 2002 in Oregon, and from 25% in 1997 to 82% in 2002 in Washington. Age-specific HZ incidence rates in KPNW during 1997-2002 were compared with published rates in the Harvard Community Health Plan (HCHP) during 1990-1992. The overall HZ incidence rate in KPNW during 1997-2002 (369/100,000 person-years) was slightly higher than HCHP's 1990-1992 rate when adjusted for age differences. For children 6-14 years old, KPNW's rates (182 for females, 123 for males) were more than three times HCHP's rates (54 for females, 39 for males). This increase appears to be associated with increased exposure of children to oral corticosteroids. The percentage of KPNW children exposed to oral corticosteroids increased from 2.2% in 1991 to 3.6% in 2002. Oregon residents had slightly higher steroid exposure rates during 1997-2002 than Washington residents. There were significant increases in HZ incidence rates in Oregon and Washington during 1997-2002 among children aged 10-17 years, associated with increased exposure to oral steroids.